Cobalt nanoparticles cause allergic contact dermatitis in humans - Midander, Klara; Werner, Paulina; Isaksson, Marléne; Wisgrill, Lukas; Lidén, Carola; Fyhrquist, Nanna; Julander, Anneli (British journal of dermatology (1951), 2023)
Cobalt (Co) causes allergic contact dermatitis (ACD) and the emerging use of Co nanoparticles (CoNPs) warrants gaining further insight into its potential to elicit ACD in sensitized individuals. The aims of the study were to clarify to what extent CoNPs may elicit ACD responses in participants with Co contact allergy, and to evaluate whether the nanoparticles cause a distinct immune response compared with cobalt chloride (CoCl2) in the skin reactions. Fourteen individuals with Co contact allergy were exposed to CoNPs, CoCl2, a Co-containing hard-metal disc (positive control), and an empty test chamber (negative control) by patch testing. Allergic responses were evaluated clinically by a dermatologist at Days 2, 4 and 7. At Day 2, patch-test chambers were removed, and remaining test-substance and skin-wipe samples were collected for inductive-coupled plasma mass spectrometry (ICP-MS) analysis. Additionally, skin biopsies were taken from patch-test reactions at Day 4 for quantitative real-time polymerase chain reaction analysis, histopathology and ICP-MS analysis of Co skin penetration. Patch testing with CoNPs elicited allergic reactions in Co-sensitized individuals. At all timepoints, clinical assessment revealed significantly lower frequencies of positive patch-test reactions to CoNPs compared with CoCl2 or to the positive control. CoNPs elicited comparable immune responses to CoCl2. Chemical analysis of Co residues in patch-test filters, and on skin, shows lower doses for CoNPs compared with CoCl2. CoNPs potently elicit immune responses in Co-sensitized individuals. Even though patch testing with CoNPs resulted in a lower skin dose than CoCl2, identical immunological profiles were present. Further research is needed to identify the potential harm of CoNPs to human health.